2018
DOI: 10.1108/jmlc-08-2015-0034
|View full text |Cite
|
Sign up to set email alerts
|

Is tackling Trade Based Money Laundering (TBML) through stricter reporting regulation the most effective response?

Abstract: Purpose This paper (written in August 2015) aims to discuss the regulatory approach to detecting and preventing trade-based money laundering (TBML) by using the example of Financial Crimes Enforcement Network (FinCEN) and its use of geographic targeting orders. Design/methodology/approach The paper uses both theoretical and empirical reports on TBML to explore whether increased regulation will ultimately achieve the ends it claims to offer. Findings The main findings from the analysis are that increased re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, AML regulations might come with some unintended consequences such as banks exiting from providing services to firms or clients perceived to come from high‐risk segments of the economy or countries (Lowery & Ramachandran, 2015; Naheem, 2018). Again, Mohammad et al (2016) provided evidence that AML regulations impact banking secrecy, increase service cost, negatively affect the volume of deposits and act as obstacles to attracting capital.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, AML regulations might come with some unintended consequences such as banks exiting from providing services to firms or clients perceived to come from high‐risk segments of the economy or countries (Lowery & Ramachandran, 2015; Naheem, 2018). Again, Mohammad et al (2016) provided evidence that AML regulations impact banking secrecy, increase service cost, negatively affect the volume of deposits and act as obstacles to attracting capital.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Another study found that TBML can have significant economic and social impacts, such as reducing tax revenues, distorting trade patterns and undermining the competitiveness of legitimate businesses (Hataley, 2020; Naheem, 2019). Another study looked at the impact of TBML on the global financial system and found that it can lead to significant financial losses for governments and businesses and contribute to economic instability and corruption (Naheem, 2018).…”
Section: Exploring the Literaturementioning
confidence: 99%
“…Meanwhile, Hoffmann (2012) describes carousel fraud as a scheme whereby criminals fraudulently claim value-added tax (VAT)benefits from the government without physically transporting goods. In recent years, Naheem (2018) and Hataley (2020) have documented the use of a method called Black Market Peso Exchange (BMPE), which operates similarly to hundi and is used worldwide, although the term “BMPE” is typically used in Latin America and the USA. These methods have made it increasingly difficult to distinguish TBML from smuggling, as physical inspection of every shipment is impractical, and post-clearance audits may not reveal discrepancies in imported goods.…”
Section: Exploring the Literaturementioning
confidence: 99%
See 2 more Smart Citations